2023
DOI: 10.1111/cns.14295
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ANXA2 activity attenuates epileptic susceptibility and GluA1 phosphorylation

Limin Ma,
Qingyuan Wu,
Jinxian Yuan
et al.

Abstract: IntroductionAnnexin A2 (ANXA2) participates in the pathology of a variety of diseases. Nevertheless, the impact of ANXA2 on epilepsy remains to be clarified.AimsHence, the study aimed at investigating the underlying role of ANXA2 in epilepsy through behavioral, electrophysiological, and pathological analyses.ResultsIt was found that ANXA2 was markedly upregulated in the cortical tissues of temporal lobe epilepsy patients (TLE), kainic acid (KA)‐induced epilepsy mice, and in a seizure‐like model in vitro. ANXA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…After tail vein injection of neuronal EVs for 48 h, 20 mM kainic acid (KA) (50 nL, Sigma-Aldrich) was injected into the CA1 region of the unilateral hippocampus to establish an epilepsy mouse model Ma et al, 2023). Mice were placed under a videotracking instrument after KA injection, and spontaneous recurrent seizures (SRSs) were recorded for a period of 28 days.…”
Section: Generation Of a Kainic Acid Epilepsy Model And Behavioral Re...mentioning
confidence: 99%
“…After tail vein injection of neuronal EVs for 48 h, 20 mM kainic acid (KA) (50 nL, Sigma-Aldrich) was injected into the CA1 region of the unilateral hippocampus to establish an epilepsy mouse model Ma et al, 2023). Mice were placed under a videotracking instrument after KA injection, and spontaneous recurrent seizures (SRSs) were recorded for a period of 28 days.…”
Section: Generation Of a Kainic Acid Epilepsy Model And Behavioral Re...mentioning
confidence: 99%
“…ANXA2 has been shown to have a pivotal role in epilepsy. A study demonstrated that ANXA2 plays a significant role in regulating excitatory synaptic activity mediated by the GluA1 subunit of AMPA receptor [37]. Elevated ANXA2 expression was detected in epilepsy patients and models, both in vivo and in vitro.…”
Section: Role Of Annexins In Neurological Disorders Of the Cnsmentioning
confidence: 99%